2023
DOI: 10.2807/1560-7917.es.2023.28.7.2200724
|View full text |Cite
|
Sign up to set email alerts
|

Higher risk of SARS-CoV-2 Omicron BA.4/5 infection than of BA.2 infection after previous BA.1 infection, the Netherlands, 2 May to 24 July 2022

Abstract: Background In summer 2022, SARS-CoV-2 Omicron BA.5 became dominant in Europe. In vitro studies have shown a large reduction of antibody neutralisation for this variant. Aim We aimed to investigate differences in protection from previous infection and/or vaccination against infection with Omicron BA.4/5 vs BA.2. Methods We employed a case-only approach includi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…This may be attributed to incomplete responses to the questionnaires from affected individuals, preventing us from drawing additional conclusions. While our data do not permit the differentiation of symptomatic cases between vaccinated and unvaccinated individuals, other studies have indicated a higher likelihood of infection among the unvaccinated [ 9 , 26 ]. Our findings underscore the need for additional information regarding the quantity and timing of vaccinations.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…This may be attributed to incomplete responses to the questionnaires from affected individuals, preventing us from drawing additional conclusions. While our data do not permit the differentiation of symptomatic cases between vaccinated and unvaccinated individuals, other studies have indicated a higher likelihood of infection among the unvaccinated [ 9 , 26 ]. Our findings underscore the need for additional information regarding the quantity and timing of vaccinations.…”
Section: Discussioncontrasting
confidence: 76%
“…In previous waves, including the Delta variant and those preceding Omicron, a significant number of individuals were not vaccinated. However, vaccination, particularly booster shots, plays a crucial role in providing protection against severe Omicron infections and the need for hospitalization [ 25 , 26 , 27 , 28 ]. Nevertheless, the vaccination data within our study are limited, given the relatively high number of unreported cases.…”
Section: Discussionmentioning
confidence: 99%
“…During the study period, sequentially Omicron BA.1, BA.2, BA.5 and to a lesser extent BA.4 caused the majority of the infections in the Netherlands. In previous Dutch studies, vaccine effectiveness was not significantly different between Omicron subvariants but previous BA.1 infections conferred lower protection to BA.4/5 compared to BA.2 (18, 19). For infections before the study period, the variant of infection is not known for certain, and variants are highly correlated with calendar time, thus complicating disentangling effects of variants and time since infection.…”
Section: Discussionmentioning
confidence: 69%
“…Compared to the BA.2 spike protein, the BA.4 and BA.5 sequences contain two additional amino acid changes (L452R and F486V), one deletion (69-70del) and one reversion (R493Q). These two variants were shown to have a higher infection rate in vaccinated or previously infected people [16, 22, 23] and a higher risk of hospitalization relative to BA.1 [10, 24].…”
Section: Introductionmentioning
confidence: 99%